Question 94: On Philosophy as Subversion, In Response to Dieter Misgeld - Gaon, Stella (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2017)
Dieter Misgeld: A Philosopher’s Journey from Hermeneutics to Emancipatory Politics, by Hossein Mesbahian and Trevor Norris (2017), is a book-length transcript of a set of wideranging and extensive conversations with Professor Emeritus Dieter Misgeld. These interviews were conducted in 2005, on the occasion of his retirement from teaching at the Ontario Institute for Studies in Education at the University of Toronto. The “journey” referenced in the title reflects the sharp distinction between philosophy and politics that appears to inform Misgeld’s views throughout the text. In response to Misgeld, I propose that, while his understanding of philosophy as apolitical or quietist arguably holds on a narrow definition of the term “philosophy,” this definition forecloses a more radical understanding of philosophy as critique. A deeper and broader conception of philosophy as “theory,” I submit, can and should be drawn from the work of first generation Frankfurt School theorists Max Horkheimer and Theodor Adorno. Properly conceived and undertaken, philosophy as critical theory can and does subvert political power, albeit not in ways that one might predict on the basis of the customary separation of theory and practice. I refer to numerous moments of the discussion to make this case so as to convey the breadth and richness of the book.